Student-led documentation of COVID-era education: a study of graduate programs on the human dimensions of oceans - Potter, Caroline; Hiserman, Luke; Papp, Gregory; Viswanathan, Harshitha; Huff, Leah E. (Frontiers in Education, 2023)
This communication highlights the major actionable findings from 27 interviews of students in master’s programs that explore the human dimensions of oceans. The overall aim of the loosely structured conversations was to understand how COVID-19 impacted the interviewee’s educational experience, what was helpful to them, and how their experience could have been improved. From these voices, we developed 24 recommendations for universities and programs. Specifically, we found that diversity, equity, and inclusion (DEI) should be a high priority as it supports students and a program’s resilience.